Evaluation of radioactive contamination of radon gas inside and outside the building of the College of Education - Iraqi University – Iraq - muslim, raafat AbdulHasan (Institut Teknologi Bandung, 2024)
Radon gas is a major indoor air pollutant, is found inside and outside buildings, and is the main cause of lung cancer. Therefore, determining its concentration levels and the dose resulting from inhalation of this gas is important for the public health of people inside buildings. The aim of the research includes measuring radon gas concentrations in the air inside and outside the building of the College of Education at Iraqi University using a nuclear trace detector (CR-39). The detector (1x2) cm2 was exposed for a full month during the winter because this period roughly represents the official working hours at the college. It is clear from the results of the study that the concentrations of radon gas inside buildings are higher than their concentrations outside buildings, and this increase in concentration is due to the fact that the walls of buildings are the main source of radon generation inside buildings, as it was shown that building materials have played an important role in increasing the concentrations of radon gas inside buildings in addition to the age of the buildings and the height above ground level. The annual equivalent dose values for exposure to radioactive radon gas and its effect on the lungs ranged between 0.43 and 1.34 mSv/y and an average of 0.86 mSv/y. These values are the lowest allowed by ICRP (3-10) mSv/y.